Processo autoformativo de professores: a escrita de si como reconhecimento da formação numa perspectiva emancipatória - Pinheiro, Arleide Maia (Brasil, 2022)
This dissertation proposes, from the perspective of training research, to understand and understand the self-training process of teachers by writing themselves as an emancipatory proposal. This perspective considers recovering historical conceptions of formation through life histories, its plural process in the personal and professional constitution of the teacher, through which, walking towards oneself through self writing, reveals the self-training process inferring that, through self-knowledge, the paths of formation.This discovery contributes to teacher education, as well as advances towards the recognition of new training models in which the teacher gains agent status in an emancipatory social-historical project. Thus, the research was developed based on the objectives: a) To understand and understand the resignification of being a teacher in a self-training process, viewed in a multifactorial and complex dynamic of life; b) To analyze the training device, Ateliê Biographical de Projeto, as an educational product that promotes the subject of change and knowledge; c) Demonstrate the methodological path of the research, identifying the trajectory of the Ateliê Biographical de Projeto as an adequate methodology for teacher training, from the perspective of research-training; d) Interpret the contributions of the Biographical Project Workshop as a training device from/for oneself; e) Evaluate the educational product of this dissertation, from its insertion in the practice of teachers in service.Oriented to answer the initial problem, which is: How do teachers recognize, reflect and re-signify themselves, in their self-training processes, from a biographical studio? The theoretical construct of the research is based on the conception that training is a processual construction based on the individual's experiences in their plural singularity, woven into the interrelationships between self and hetero. This process constitutes a trainer, by reframing, through the (auto)biographical method, the teaching practice, as the teacher gains the condition of agent in the process that formed him.The research methodology used in this project was the Ateliê Biographical de Projeto, since it meets the prerogatives of research-training when it allows, through the life history bias, to enter memories and extract from them the core of meaningful and formative experiences. This construction was analyzed in the light of Ricoeurian Hermeneutics, which makes it possible to mediate through the text (the writing of oneself) meanings contained in the elements of life represented by the symbolic universe of language. Such meanings converge to the understanding of (self) formation intertwined with individual ontology, which was confirmed by the Biographical Atelier of Project as a training strategy, whose analysis was conducted by the participants, who under this perspective analyzed the (auto)biographical records. In this way, the IFAM/CPA professors, participating in this investigation, were able to re-signify themselves in a space that allowed them, from their personal experiences, new perspectives on the profession; an emancipatory perspective in the sense of commitment to the ability to think critically associated with a collective-reflective attitude towards changes in education.